MODEL PERENCANAAN KOMUNIKASI HUMAS POLRESTA SURAKARTA DALAM MEMBANGUN CITRA MELALUI PENYEBARAN INFORMASI COVID-19 DI INSTAGRAM - Awal, Awal Uddin Sodri; Wisudawanto, Rahmat; Ningsih Rahayu Putri, Sofia (JURNAL KOMUNITAS, 2023)
Covid-19 was a major threat to the people of Surakarta City. Polresta Surakarta provided Covid-19 information to the public through Instagram. Polresta Surakarta conveyed information related to Covid-19, including prokes, vaccinations, and social assistance for the community. The purpose of this study was to explain the application of the public relations communication planning model of polresta Surakarta in building an image through the dissemination of Covid-19 information on Instagram. The research used qualitative descriptive methods. Meanwhile, the data collection method uses documentation, namely screenshots of IG Polresta Surakarta posts and interviews with public relations staff of Polresta Surakarta. In addition, respondents were selected based on predetermined criteria. The results of this study show that the communication model carried out by the surakarta police public relations in spreading Covid-19 information on Instagram media is quite effective, although there are limitations such as frequent repeating sentences in captions in some uploads. Based on this communication model, the image of the Surakarta Police is considered good for the community.